External quality assessment to support the WHO ProSPeRo study for the evaluation of two dual HIV/syphilis point-of-care tests in seven countries - Weiping Cao; Yetunde F. Fakile; Mayur R. Shukla; Kevin Pettus; Kathryn Lupoli; Jaeyoung Hong; Allan Pillay; Ranmini Kularatne; Hicham Oumzil; Valeska Padovese; Nigel Sherriff; Isaac SSewanyana; et al. (BMC Infectious Diseases, 2024)
Abstract Background Sexually transmitted infections (STIs) such as syphilis and HIV remain to be a significant public health issue worldwide. Dual rapid point-of-care tests (POCTs) have shown promise for detecting antibodies to HIV and syphilis but have not been fully evaluated in the field. Our study supported the WHO ProSPeRo study on Sexually Transmitted Infection Point-of-Care Testing (STI POCT) by providing external quality assessment (EQA) for HIV and syphilis testing in reference laboratories and their associated clinical sites in seven countries. Methods HIV/syphilis serum liquid and dried tube specimen (DTS) panels were prepared by CDC. Liquid panels were distributed to the reference laboratories for three rounds of testing using commercially and locally available laboratory-based serological tests. DTS panels were sent to the clinical testing sites for 8 rounds of POC testing using the Abbott SD BIOLINE HIV/Syphilis Duo test (hereafter referred to as SD BIOLINE) and the Chembio Dual Path Platform (DPP) HIV-Syphilis assay. EQA panels were tested at CDC using the Rapid Plasma Reagin (RPR) test and the Treponema pallidum Particle Agglutination assay (TP-PA) for syphilis antibodies. Genetic Systems HIV-1/HIV-2 Plus O EIA, Geenius HIV Supplemental Assay and the Oraquick Advance HIV test were used to detect HIV antibodies in the EQA panels. Results from the reference laboratories and POCT sites were compared to those obtained at the CDC and a percentage agreement was calculated. Results Qualitative RPR and TP-PA performed at the reference laboratories demonstrated 95.4–100% agreement with CDC results while quantitative RPR and TP-PA tests demonstrated 87.7% and 89.2% agreement, respectively. A 93.8% concordance rate was observed for qualitative HIV testing in laboratories. EQA testing at clinical sites using dual tests showed 98.7% and 99.1% agreement for detection of HIV antibodies and eight out of 10 sites had > 95.8% agreement for syphilis testing. However, two clinical sites showed only 65.0–66.7% agreement for SD BIOLINE and 84.0–86.7% for DPP, respectively, for syphilis testing. Conclusions Overall, laboratories demonstrated high EQA performance in this study. Both HIV/syphilis POCTs gave expected results in the clinic-based evaluations using DTS. However, testing errors were identified in a few testing sites suggesting the necessity for continuous training and monitoring the quality of POC testing.